Energy Efficiency of Oat:Pea Intercrops Affected by Sowing Ratio and Nitrogen Fertilization - Gerhard Moitzi; Helmut Wagentristl; Hans-Peter Kaul; Jaroslav Bernas; Reinhard W. Neugschwandtner (Agronomy, 2022)
This study analyzed energy input (direct and indirect), energy output, net-energy output, energy use efficiency, energy intensity, and the energy productivity of oat:pea intercrops as affected by sowing ratio (oat:pea (%:%): 100:0, 75:25, 50:50, 25:75, 0:100) and nitrogen (N) fertilization (0, 60, 120 kg N ha−1). The two year field experiment was conducted on a calcaric Chernozem soil in the north-western part of the Pannonian Basin. The results for grain yield showed that pure stands of oat and pea had a higher energy use efficiency and energy intensity than intercrops, indicating that pure stands used the growing factors more efficiently than intercrops. The energy use efficiency was higher in pure pea than pure oat. The energy productivity for the above-ground biomass production was much more affected by the factor N fertilization than by the factor sowing ratio. The highest energy productivity of grain N yield and above-ground biomass N yield was achieved in pure pea stands (0:100). N in plant residues of the zero N fertilization variant required 68% lower technical energy than N from mineral fertilizer. The sowing rate of the intercrops is a management tool to trade-off between the benefits of the in-field biodiversity and energy efficiency.